Redescription of Polichnodes americana Giglio-Tos, 1898 (Orthoptera: Tettigoniidae) with a new record and habitat notes from Brazilian Amazon Rainforest - Mendes, Diego Matheus de Mello; Sobral, Rafael; Silva Neto, Alberto Moreira da (Zootaxa, 2019)
In this work it was made the redescription of male of Polichnodes americana including new traits as internal genitalia and morphology of stridulatory files. Also it was recorded for the first time the distribution of this species to Brazil, in Amazonas, and notes on habitat. Copyright © 2019 Magnolia Press
Keywords: Adult; Amazona; Genital System; Habitat; Male; Nonhuman; Rainforest; Tettigoniidae; Animals Distribution; Animal; Male; Orthoptera; Phenotype; Rainforest